Relationship Between CHA2DS2-VASC Score With CIN For AMI Patients After PCI - Herman Wiliam Parlindungan (Talenta Publisher, 2019)
The CHA2DS2-VASC score has been reported recently to predict adverse clinical outcomes so is CIN in patients with AMI regardless of having AF. We investigated relationship between CHA2DS2-VASC score with CIN in patients who underwent PCI strategies. This is a study of 40 patients with and underwent PCI. The CHA2DS2-VASC score was calculated for each patient. From this study 16 cases(18.82%) of CIN were diagnosed. CIN was defined as rise in serum creatinine>0,5mg/dL or>25% increase in baseline within 24h after PCI. In the ROC curve analysis,the cut-off value of CHA2DS2-VASC score in the prediction of CIN was>4(sensitivity:56.25%,Specificity:87.5%)(AUC0.698,95%:CI1.460-6.163,p=0.003) and has a significant association with CIN(R20.485). We also identified Hb level<12mg/dL as an independent predictor of CIN with (RR3.44,95%:CI1.816-6.532,p<0.001). The CHA2DS2-VASC score was positively associated with CIN. Therefore,it can be used as a simple and reliable tools to predict CIN in AMI patients who underwent PCI.